New records of the Flat-headed Cat Prionailurus planiceps (Vigors & Horsfield, 1827) (Mammalia: Carnivora: Felidae) in western Sarawak, Malaysia - Mohd Azlan Jayasilan, Abdul Gulam Azad; Syaza, Jailan Thaqifah (2020)
The Endangered Flat-headed Cat is threatened due to loss of lowland and wetland habitats. Its elusive nature and low density occurrence make field sampling difficult. Compilation of records from both camera trapping and direct observation can provide important updates to its current distribution in Sarawak. In western Sarawak, the Flat-headed Cat was recorded in Maludam National Park, in Ulu Sebuyau National Park and at Sarawak River, which are the first confirmed records. The Flat-headed Cat appears to inhabit swamp forest in pristine protected areas as well as near human settlements. The conservation of peat swamp forests is crucial for its long-term persistence.